Exploring the ASPIRE Framework: Enhancing Assessment Literacy through Inquiry-Based Teacher Education - Quileste, Ronald; Estacio, Maria Leah Paola; Pagara, Charity Rose (International Journal of Education and Teaching Zone, 2025)
Assessment literacy remains underdeveloped in many teacher education programs, with limited use of inquiry-based approaches. No empirical studies have applied the 5Es model specifically to assessment education, particularly in resource-constrained contexts. This mixed-methods study introduces the ASPIRE Framework (Assessment through Structured Pedagogy, Inquiry, and Reflective Engagement), an adaptation of the 5Es model integrating constructivist principles and the Filipino value of bayanihan. Implemented in a Philippine teacher education course (n = 29 pre-service teachers), ASPIRE was evaluated through surveys, a validated pretest-posttest, interviews, and assignment analysis. Engagement remained consistently high across phases (M = 3.64–3.75/4), and learning scores improved significantly by 9.22 points (Z = –3.96, p < 0.001, r = 0.73), indicating a substantial impact. Qualitative findings highlighted clarity, practicality, and strong collaborative learning, though time constraints limited group activities during the Explore phase. The framework’s low-resource design suggests adaptability in similar Southeast Asian settings. While results provide preliminary evidence that culturally responsive, inquiry-driven pedagogy can enhance assessment literacy, the small sample and single-course context limit generalizability. Future research should examine scalability across disciplines, compare ASPIRE with traditional approaches, and explore adaptations for diverse educational and cultural contexts.